Permodalan Nasional Berhad (PNB) Commercial Sdn Bhd / Muhamad Syahmi Mukti - Mukti, Muhamad Syahmi (Faculty of Business and Management, 2023)
This report provides a comprehensive overview of the six-month internship I completed at Permodalan Nasional Berhad (PNB) Commercial Sdn. Berhad in Kuala Lumpur, from 1st March 2023 to 15th August 2023. The report covers various aspects, starting with my resume, followed by an introduction to PNB Commercial Sdn. Berhad, including its vision, mission and organizational structure. A detailed SWOT analysis of PNB Commercial Sdn. Berhad is also included. The primary focus of this report is to analyze the SWOT factors encountered during my six-month industrial training, with special emphasis on the tasks I completed, knowledge I acquired and the experience I gained within the Sales and Leasing department of PNB Commercial Sdn. Berhad. During the internship, I was introduced to the company's systems, work procedures and most importantly, the work culture and environment. Furthermore, this report presents valuable suggestions and recommendations to address the identified weaknesses. I learned how to overcome challenges by applying communication, problem-solving and management skills that I acquired through practical experience during the internship. As a result of this internship, I developed a deeper understanding of professional work behavior, gained practical experience in a corporate setting and obtained a comprehensive understanding of how to effectively function within a company. Overall, the point of this report is clear and relatable, as it provides a detailed overview of the internship experience, including the analysis of strengths and weaknesses encountered during the training and the valuable skills and knowledge acquired. However, it could be further improved by breaking down the paragraphs into smaller, more digestible chunks and adding a concluding section summarizing the key takeaways and future implications of the internship experience.